The purposes of The Holy Qura’n in the instruments of gaining wealth - Lutf, Mohammed Abdulrab Sharaf; Hama, Zakaria (Arab Journal for Sciences and Research Publishing, 2023)
The study aimed to introduce the purposes of the Qur’an regarding the financial instruments for gaining wealth, whether permissive or forbidden. The researcher used the inductive approach in tracing the verses of the Qur’an that related to earning wealth, and deducing the purposes from it. These were the objective limits of the study, contenting himself with one or two verses to prove legitimacy and purpose and suiting the scope of the research. The study concluded: 1) The Qur’an proved the legitimacy of gaining wealth and called for it in many verses, 2) The Qur’an legislated gaining wealth through 13 financial instruments, 3) The financial instruments that were permissible for gaining wealth without compensation, which the Holy Qur’an had specified were 9 in number, which: inheritance, zakat, testament, gift, war assets, minerals, stray items, and what is permissible over which no one has authority, 4) The Qur’an affirmed working, dowry, compensation, remuneration, protection fee as legitimate financial means of gaining wealth, 5) The Qur’an forbade 6 financial instruments for gaining wealth, which were: theft, usury, monopoly, bribery, gambling, and coercion, 6) Every financial instrument had purposes that determine the reason for its legality or illegality, 7) The prominent purposes of the legitimate financial instruments of gaining wealth were: Calling for Halal good- gain, work and to produce, Proving slavery to Allah- the Almighty, and the intention to eliminate critical situation and hardship by securing the needs of the individual, family and state, 8) The prominent purposes of the Qur’an that prevented from illegitimate financial instruments were: to prevent financial injustice, to maintain wealth, to respect the rights of others, and to prove slavery to Allah- the Almighty- by staying away from the illegitimate financial instruments of gaining wealth. In light of the aforementioned results, the researcher recommended the following: 1- Educational and Academic institutions interested in Islamic sciences have to develop specific content to the financial objectives of the Qur’an within academic curricula. 2- Islamic financial institutions need to hold seminars and conferences to discuss contemporary financial issues with a purposeful vision, whether permissible or prohibited.